2006
DOI: 10.5367/000000006778536729
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Efficiency of Cotton Production on the Harran Plain, Turkey

Abstract: Compared with results from other studies of farm production in developing countries, this study finds that the sample of 54 cotton farmers located on the Harran Plain, Turkey, are producing at a high level of efficiency. Nevertheless, 72% of the farms are using inefficient levels of inputs. A statistically significant, positive relationship between farmers' education and on-farm technical efficiency underscores the need for public investment in rural education. Chemical, urea, tractor and labour inputs are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…coelli et al (2002) found that younger rice farmers in Bangladesh were more efficient than the older rice farmers. Binici et al (2006) found that age has no statistically significant effect on the cotton farms technical efficiency in Turkey.…”
Section: Methodsmentioning
confidence: 90%
“…coelli et al (2002) found that younger rice farmers in Bangladesh were more efficient than the older rice farmers. Binici et al (2006) found that age has no statistically significant effect on the cotton farms technical efficiency in Turkey.…”
Section: Methodsmentioning
confidence: 90%
“…Given that this sample consists mainly of small farm enterprises, one would not expect that the study area cotton production exhibits diseconomies of scale. This expectation is in fact reasonable since previous studies on agricultural productivity in developing countries support an inverse relationship between farm size and productivity (Bery & Cline 1979;Barrett 1996;Helfand et al 2004;Grabowski et al 1990;Binici et al 2006). Even though different findings are available in the literature (e.g., Townsend et al 1998), similar results in Turkey are reported by Cinemre & Ceyhan (1998), i.e., using a linear technology, they found that mix type farms and vegetable farms demonstrate increasing returns to scale.…”
Section: Resultsmentioning
confidence: 59%
“…In a most recent study of Binici et al (2006) it was found that the majority of sampled farmers from the Harran Plain use inputs at inefficient levels. Moreover, the common practice of over irrigation on the Harran Plain is considered to be the major cause of elevated soil salinity (Cullu 2003), arising from shallow groundwater table (Cullu et al 2002), and leading to considerable reductions in cotton production (Cullu et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The mean efficiency is estimated around 65 % for cotton production when 8 years and 14 cities are taken into account. Some examples of efficiency studies for cotton production are Binici et al (2006) and Gul et al (2009), where both studies calculated efficiency scores of 79 %. Although one can claim such differences may depend on the sample differences and climatic conditions that vary during the time period, our analysis show that the omission of premium payment factor from the regression as well may produce such difference between the efficiency scores.…”
Section: Resultsmentioning
confidence: 99%